The Ikat Weaving Industry in Kediri: Characteristics and Strategies for Development, 1966-2014 - Feri Sofiantoro; Endang Susilowati; Alamsyah Alamsyah (Diponegoro University, 2022)
This article analyses the developments and strategies experienced by the ikat weaver in Kediri, especially in the Village Bandar Kidul, District Mojoroto. This study used the critical history method. It emphasizes primary sources in the form of written sources from newspapers and the oral history method. According to the result, ikat weaving in Bandar Kidul began to develop when a Chinese resident, Freddy Jie, in the 1950s opened the ikat weaving business which affects the livelihoods of the residents of Bandar Kidul. They have depended on one sector of livelihood and the industry has begun to grow. Due to its motifs and production tools, the ikat production from the village of Bandar Kidul has a good and potential market demand. However, the monetary crisis in 1997-1998 hit the industry and began to down. From the end of the 1970s to the late 1990s, the Bandar Kidul ikat craft began to experience a downturn due to being unable to compete with factory-made woven fabrics and the absence of successor regeneration after most of the business’ founders died. However, entering the mid-2000s, the future of the ikat industry was bright because the local government intervened in the industry. Some pieces of training had been held to improve the capabilities of the ikat weaver under dominated by modern equipment.